The role of social media activities towards brand image and its impact on satisfaction, emotional attachment, and repurchase intention in beauty products - Yunna, Weng; Berlianto, Margaretha Pink (Institute of Computer Science (IOCS), 2025)
The beauty product industry in Indonesia has great potential, so it is important for manufacturers to be able to maintain loyal consumers in order to continue to grow. This study aims to test the effect of social media benefits, social media rewards, social media interactivity, and perceived quality on brand image, as well as the effect of brand image on emotional attachment, repurchase intention and satisfaction. Likewise with the effect of satisfaction on repurchase intention and brand commitment. This study was conducted quantitatively with a causal approach. This study was conducted on 233 Somethinc consumers obtained using purposive sampling, namely sampling with the criteria of consumers who have used Somethinc products at least once. The results of this study indicate that social media benefits, social media rewards and perceived quality have a significant and positive effect on brand image, while social media interactivity has no effect on brand image. The results also show that brand image has a significant effect on emotional attachment, repurchase intention and satisfaction, as well as a significant and positive effect of satisfaction on repurchase intention and brand commitment